2008
DOI: 10.1521/psyc.2008.71.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Psychodynamic Approaches to Treatment of PTSD and Trauma: A Review of the Empirical Treatment and Psychopathology Literature

Abstract: Reviews of currently empirically supported treatments for post-traumatic stress disorder (PTSD) show that despite their efficacy for many patients, these treatments have high nonresponse and dropout rates. This article develops arguments for the value of psychodynamic approaches for PTSD, based on a review of the empirical psychopathology and treatment literature. Psychodynamic approaches may help address crucial areas in the clinical presentation of PTSD and the sequelae of trauma that are not targeted by cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 16 publications
3
72
0
4
Order By: Relevance
“…However, in a recent meta-analysis on treatments of PTSD in children an incremental efficacy of EMDR has been found when compared to other forms of PTSD treatments (Rodenburg, Benjamin, de Roos, Meijer, & Stams, in press). In contrast, although widely used, there is as yet no empirical evidence for a clinically important effect of psychodynamic therapy on PTSD (Schottenbauer, Glass, Arnkoff, & Gray, 2008;National Collaborating Centre for Mental Health, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent meta-analysis on treatments of PTSD in children an incremental efficacy of EMDR has been found when compared to other forms of PTSD treatments (Rodenburg, Benjamin, de Roos, Meijer, & Stams, in press). In contrast, although widely used, there is as yet no empirical evidence for a clinically important effect of psychodynamic therapy on PTSD (Schottenbauer, Glass, Arnkoff, & Gray, 2008;National Collaborating Centre for Mental Health, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that it is not necessarily OEF/OIF/OND status that predicts higher dropout, but rather the Veterans' ages, which may be associated with competing life responsibilities that inhibit treatment engagement. Schottenbauer, Glass, Arnkoff and Gray (2008) argued that research on alternative approaches to PTSD treatment was needed based on the large nonresponse and dropout rates found in treatment studies using Prolonged Exposure and Cognitive Processing Therapy. As such, researchers have developed novel treatments for PTSD using a variety of technologies.…”
Section: Written Exposure Therapy As Step One In Reducing the Burden mentioning
confidence: 99%
“…All treatments that have been systematically evaluated in controlled trials require manuals that specify therapist competences. These include not only CBT (e.g., McDonagh et al, 2005) but also experiential (e.g., Paivio & Nieuwenberg, 2001) and psychodynamic therapies (such as those reviewed by Schottenbauer et al, 2008).…”
Section: Competences and Metacompetencesmentioning
confidence: 99%